2017
DOI: 10.1111/1462-2920.13896
|View full text |Cite
|
Sign up to set email alerts
|

Sorting nexin (MoVps17) is required for fungal development and plant infection by regulating endosome dynamics in the rice blast fungus

Abstract: Vps17 is a sorting nexin (SNX) and a component of the retromer, a protein complex mediating retrograde vesicle transport between endosomes and the trans-Golgi network. However, its role in the development and pathogenicity of filamentous fungi such as the rice blast fungus (Magnaporthe oryzae) remains unclear. We investigate the functional relationship between the SNX and the cargo-selective complex (CSC) of the fungal retromer by genetic analysis, live cell imaging and immunological assay. Our data show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 53 publications
(109 reference statements)
2
20
0
Order By: Relevance
“…For autophagy assay, 4×10 4 /ml conidial suspension were cultured in liquid CM medium for 16 h. Mycelia were harvested and washed twice with water and then transferred to nitrogen-limiting medium (MM-N) in the presence of 2 mM PMSF for 8 h. GFP-FgAtg8 were visualized and total proteins were extracted at 0 h and 8 h after starvation. For immunoblot analysis of GFP-fusion-proteins from cellular extracts, equal concentrations of total proteins were isolated and analyzed by immunoblot detection with the anti-GFP (GFP-Tag Mouse mAb, Abmart, China) and anti-actin antibodies (Actin-Tag Mouse mAb, Abmart, China) following a previous report [ 66 ]. For immunoprecipitation, total proteins were isolated and incubated with 30 μL of GFP-Trap_A beads according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…For autophagy assay, 4×10 4 /ml conidial suspension were cultured in liquid CM medium for 16 h. Mycelia were harvested and washed twice with water and then transferred to nitrogen-limiting medium (MM-N) in the presence of 2 mM PMSF for 8 h. GFP-FgAtg8 were visualized and total proteins were extracted at 0 h and 8 h after starvation. For immunoblot analysis of GFP-fusion-proteins from cellular extracts, equal concentrations of total proteins were isolated and analyzed by immunoblot detection with the anti-GFP (GFP-Tag Mouse mAb, Abmart, China) and anti-actin antibodies (Actin-Tag Mouse mAb, Abmart, China) following a previous report [ 66 ]. For immunoprecipitation, total proteins were isolated and incubated with 30 μL of GFP-Trap_A beads according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Kim et al showed that TOR regulates some effectors for cellular survival in Aspergillus nidulans undergoing rapamycin-induced and carbon starvation-induced autophagy [15]. Furthermore, an increasing amount of research indicates that the autophagy and endocytosis pathways are also essential for conidial and appressorium formation [16][17][18][19].…”
Section: Interactions Between Pathogenic Fungi and Plantsmentioning
confidence: 99%
“…In mammals, Rab1, Rab5, and Rab11 play important roles in the regulation of autophagy by regulating mTOR activity; specifically, these three proteins are involved in autophagosome formation and autophagosome-lysosome fusion [41]. Recent studies have also demonstrated that some endocytosisrelated genes, including MoYpt7, PoVps35, PoVps26, PoVps17, MoVps41, and MoEnd3, are involved in autophagy in M. oryzae [17,37,42,53].…”
Section: Biological Process and Function Of Autophagymentioning
confidence: 99%
See 2 more Smart Citations